The perceived influence of the elements of internal marketing on the brand image of a staffing agency group - C. Burin; M. Roberts-Lombard; H. B. Klopper (South African Journal of Business Management, 2015)
The main purpose of the study on which this article is based was to determine the influence of internal marketing on service quality as a means of improving the brand image of staffing agencies. The population of the study was the publicstaffing industry in South Africa. The sampling unit was the clients of a selected staffing brand. The selected sample of respondents was surveyed through an online self-administered survey distributed via a link in an email. The data wasanalysed using multivariate regression statistics. The application of an internal marketing approach enables staffing agencies to minimise employee turnover and increase service quality and performance, aiding staffing agencies to gainstrong brand images that result in higher levels of competitiveness and profitability. Successful internal marketing should have a positive influence on employee attitudes and actions and therefore enhance customer satisfaction and service quality. The integration of internal marketing into the organisation's overall marketing strategy is therefore critical. The purpose of such a strategy can be to ensure that the organisation recruits and trains employees to deliver on the values of the brand in order to ensure that staffing agencies strengthen their brand images.
Keywords: 650